Umur, Pendidikan dan Pekerjaan dengan Tingkat Pengetahuan Ibu Hamil tentang Tanda Bahaya Kehamilan Trimester III di BPM Choirul Mala Dan BPM Zuniawati Palembang Tahun 2017 - Aryanti Aryanti; Yesi Yesi (LPPM STIKES Al-Ma'arif Baturaja, 2018)
According to the Indonesian Demographic Health Survey (SDKI) 2012, the number of maternal deaths amounts to 359 / 100,000 live births. Maternal deaths caused by pregnant women do not know the signs of pregnancy harm Trimester III. Trimester III pregnancy is a pregnancy of 28 weeks to 40 weeks. This study aims to determine the relationship between age, education, and work with the level of knowledge of pregnant women about the signs of pregnancy trimester III. This type of research is descriptive with a cross-sectional approach using a non-random method. Primary data collection and measuring instrument used is a questionnaire. The population in this study was all trimester III pregnant women and samples were taken with accidental sampling technique conducted from April to June. Based on the result of chi-square statistic test obtained age result (p-value = 0,000), education (p-value = 0,010), and job (p-value = 0,011). The presence of age, education, and employment relationship with maternal knowledge level about the sign of third-trimester pregnancy is seen from p-value α ≤ (0.05). Where age, education, and work all have a relationship with the level of knowledge of pregnant women about the danger signs of third-trimester pregnancy.